The effect of the imposition of fines for overdue books on third and fourth year students of some selected high schools in Manila - Ajayi, Nathaniel Akinola; Picache, Ursula G.; Santiago, Ligaya S. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1983)
The education program in a school is strengthened in direct proportion to the quality of the school library service, for the school library is the keystone of a quality educational program. The purpose of this study is to determine the effect of the imposition of fines for overdue books on high school students.
The procedures include: 1) a review of the literature to determine what is so far known and done about the imposition of fines in school libraries, 2) formulation of the questionnaire, 3) selection of schools to be included and distribution of questionnaire, and 4) visit of the school libraries to interview the librarians concerning their libraries. The research tools used in collecting data are principally the questionnaire and interviews. The questionnaire contains twenty-one questions confined to the students and the library.
The study was limited to third and fourth year high school students enrolled during the second semester of the school year 1982/83 in four selected high schools in Manila. A sample of two hundred students was used to test the following hypotheses: 1) the imposition of fines makes students return books on time, 2) the rate of borrowing of books after students have been fined does not change, and 3) the imposition of fines does not have any psychological effect on students, 4) fines are not deterrent but rather a corrective measure to the students, 5) fines serve to instill discipline among students, and 6) students feel that the imposition of fines must be continued.
Based on the results of the study, the following recommendations are made: 1) the imposition of fines in the school library should be continued, 2) the amount charged should be sufficiently high to make students feel the necessity of returning books promptly, but not severe enough to cause ill-effects, 3) incentives such as prizes should be given to students who maintained good records of consistent promptness in returning books borrowed throughout the school year, 4) other ways of making students pay for their negligence should be sought, such as making them serve in the library during their free period to cover their debts, 5) the loan period should be lengthened from 7 days to 10 days, 6) the method of notification of overdue books should be revised.
It is likewise recommended that this study be replicated by using a more scientific way of obtaining respondents in order to validate the results. Another study involving bigger samples that will have a bigger population from both private and public schools may be undertaken.
Mimeographed.
Thesis (Master of Library Science)--University of the Philippines Diliman
Keywords: High school students--Philippines--Manila.; Library fines and fees--Philippines--Manila.